The politics and crisis management of animal health security - Connolly, John (Lecturer in public policy : Scotland) (Ashgate, 2015)
The Politics and Crisis Management of Animal Health Security addresses the 2001 foot and mouth epidemic in the United Kingdom - one of, if not the, most significant crises ever to face the UK farming industry. Underpinned by interviews with politicians and bureaucrats and with significant primary documentary analysis the book shows that the crisis was a critical juncture in how disease outbreaks have been planned and managed ever since. The author explores how this event affected policy and governance arrangements for managing subsequent disease-induced threats (such as avian influenza and bovine TB) and concludes by considering the 'temporality' of lesson learning by the UK government including the current and future challenges associated with managing incongruent risks (e.g., flood protection, swine flu and Ebola). This book provides students of public policy and administration with a significant illustration of how key concepts and analytical lenses from public policy can be applied to the study of the contours of practical policy change.